Pleuroparenchymal fibroelastosis in idiopathic pulmonary fibrosis: Survival analysis using visual and computer-based computed tomography assessment. (August 2021) - Gudmundsson, Eyjolfur; Zhao, An; Mogulkoc, Nesrin; Stewart, Iain; Jones, Mark G.; Van Moorsel, Coline H.M.; Savas, Recep; Brereton, Christopher J.; Van Es, Hendrik W.; Unat, Omer; Pontoppidan, Katarina; Van Beek, Frouke; et al.
Abstract: Background: Idiopathic pulmonary fibrosis (IPF) and pleuroparenchymal fibroelastosis (PPFE) are known to have poor outcomes but detailed examinations of prognostic significance of an association between these morphologic processes are lacking. Methods: Retrospective observational study of independent derivation and validation cohorts of IPF populations. Upper-lobe PPFE extent was scored visually (vPPFE) as categories of absent, moderate, marked. Computerised upper-zone PPFE extent (cPPFE) was examined continuously and using a threshold of 2·5% pleural surface area. vPPFE and cPPFE were evaluated against 1-year FVC decline (estimated using mixed-effects models) and mortality. Multivariable models were adjusted for age, gender, smoking history, antifibrotic treatment and diffusion capacity for carbon monoxide. Findings: PPFE prevalence was 49% (derivation cohort, n = 142) and 72% (validation cohort, n = 145). vPPFE marginally contributed 3–14% to variance in interstitial lung disease (ILD) severity across both cohorts. In multivariable models, marked vPPFE was independently associated with 1-year FVC decline (derivation: regression coefficient 18·3, 95 CI 8·47–28·2%; validation: 7·51, 1·85–13·2%) and mortality (derivation: hazard ratio [HR] 7·70, 95% CI 3·50–16·9; validation: HR 3·01, 1·33–6·81). Similarly, continuous and dichotomised cPPFE were associated with 1-year FVC decline and mortality (cPPFE ≥ 2·5% derivation: HR 5·26, 3·00–9·22; validation: HR 2·06, 1·28–3·31). Individuals with cPPFE ≥ 2·5% or marked vPPFE had the lowest median survival, the cPPFE threshold demonstrated greater discrimination of poor outcomes at two and three years than marked vPPFE. Interpretation: PPFE quantification supports distinction of IPF patients with a worse outcome independent of established ILD severity measures. This has the potential to improve prognostic management and elucidate separate pathways of disease progression. Funding: This research was funded in whole or in part by the Wellcome Trust [209, 553/Z/17/Z] and the NIHR UCLH Biomedical Research Centre, UK.